Redox‐Active Iron‐Citrate Complex Regulated Robust Coating‐Free Hydrogel Microfiber Net with High Environmental Tolerance and Sensitivity. (16th February 2020) - Ju, Min; Wu, Baohu; Sun, Shengtong; Wu, Peiyi
Abstract: Stretchable hydrogel microfibers as a novel type of ionic conductors are promising in gaining skin‐like sensing applications in more diverse scenarios. However, it remains a great challenge to fabricate coating‐free but water‐retaining conductive hydrogel microfibers with a good balance of spinnability and mechanical strength. Here the old yet significant redox chemistry of Fe‐citrate complex is employed to solve this issue in the continuous draw‐spinning process of poly(acrylamide‐ co ‐sodium acrylate) hydrogel microfibers and microfiber nets from a water/glycerol solution. The resultant microfibers are ionically conductive, highly stretchable, and uniform with tunable diameters. Furthermore, the presence of redox‐reversible Fe‐citrate complex and glycerol endows the fibers with good anti‐freezing, water‐retaining, and environmentally intelligent properties. Humidity and UV light can finely mediate the stiffness of hydrogel microfibers; conversely, the ionic conductance of microfibers is also responsive to light, humidity, and strain, which enables the highly sensitive perception of environmental changes. The present draw‐spinning strategy provides more possibilities for coating‐free conductive hydrogel microfibers with a variety of responsive and sensing applications. Abstract : Iron‐citrate complex–based redox chemistry allows for continuous draw‐spinning of highly stretchable, uniform, and conductive hydrogel microfiber nets with excellent freezing and dehydration resistance, tunable mechanical stiffness, and electrical sensitivity to a variety of environmental changes.